Comrades Betrayed : Jewish World War I Veterans under Hitler - Geheran, Michael, 1971- (Book collections on Project MUSE., 2020)
"Jewish veterans developed a distinctive manner of thinking and behaving as a consequence of their World War I experience, socialization in the military, and status. They embraced specific ideologies of masculinity to counter Nazi antisemitic stereotypes"--